Pengaruh Transformasi Digital di Era Society 5.0 terhadap Gaya Kepemimpinan dalam Perspektif Bela Negara - Kurniasih, Endah Tri; Putra, Adi; Veronika, Deka; Fajri, Muhammad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of National Defense awareness on leadership style, taking into account the moderation of digital transformation. The research method uses a mixed approach by analyzing quantitative data through questionnaires and qualitative data. The research results show that a strong understanding of National Defense is significant in influencing leadership style among Muhammadiyah Student Association (IMM) leaders, even though it is not supported by digital transformation as a moderating variable.